Discovery and natural history of the mussel leech Batracobdella kasmiana (Oka, 1910) (Hirudinida: Glossiphoniidae) in Russia - Bolotov, Ivan N.; Vikhrev, Ilya V.; Aksenova, Olga V.; Bespalaya, Yulia V.; Gofarov, Mikhail Y.; Kondakov, Alexander V.; Sokolova, Svetlana E. (Zootaxa, 2017)
The mussel leech Batracobdella kasmiana (Oka, 1910) (Hirudinida: Glossiphoniidae) inhabits the mantle cavity of large freshwater mussels (Sawyer 1986; Lai & Chen 2010). This specific lifestyle is unusual in leeches although a few additional parasitic species from mussels have been reported (Grizzle & Brunner 2009). The known localities of B. kasmiana are situated in Japan (Honshu), continental China and Taiwan (Oka 1910, 1917; Gee 1919; Yang 1996; Yamauchi et al. 2008; Lai & Chen 2010). The majority of records were reported from continental China, in which this species is widely distributed across the eastern half of the country from Yunnan to Beijing (Yang 1996). It has never been mentioned as a member of the Russian fauna (Lukin 1976). A few naiad species in the family Unionidae are known hosts of B. kasmiana, including Sinanodonta spp., Cristaria plicata (Leach, 1815), and Nodularia douglasiae (Griffith and Pidgeon, 1833) (Oka 1917; Yang 1996; Yamauchi et al. 2008). The biology and ecological preferences of this leech species are poorly known (Yang 1996; Yamauchi et al. 2008; Lai & Chen 2010).